Is their choice to be a juvenile with sexual behavior disorder: a study of etiological factors - YILDIZ, ALİ MURAT; ÖZDEMİR, MİRAÇ; TURAN YURTSEVER, NURŞEN (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
As juveniles become a part of a criminal justice system by committing major crimes such as sexual crimes, this may lead to both individual and social issues. To ensure an evidence-based approach to the primary prevention of sexual behavior problems, understanding the environmental risk factors in this critical period of their lives is essential. The court files dated 2014 on Juvenile with Sexual Behavior Disorder (JSBD) were obtained from Turkey Istanbul Anatolia Court House. All data were collected and statistically analyzed. In total 3777 Juveniles committed crimes in the year 2014 and 131 (3.46%) of them were JSBD cases. It was determined that 130 (99.2%) of these JSBD related crimes were males and 1(0.8%) was a female. The average age of JSBD was calculated as 15,39 +/- 1.52 years of age. Petty Sexual Assault crimes constituted the largest group of these studied cases with 45.8% (n = 60). Major Sexual Assault and Indecent Sexual Assault criminal cases followed respectively with 35.9% (n = 47) and 16% (n = 21). At the stage of assessment of the said juveniles, apart from their individual traits, the structure of their families and surroundings, education and socio-economic status taken into account.
Keywords: Sexual assault; abuse; juvenile sexual behavior disorder; juvenile; ADOLESCENTS EXPERIENCES; ASSAULT; VICTIMIZATION; PERPETRATORS; PREVALENCE; ABUSE; RISK